Gestando en zona de insolvencia: deberes del directorio ante situaciones de pérdida - Robilliard D’Onofrio, Paolo (2023)
The functions performed by the Board of Directors are delimited by the diligence and loyalty duties it maintains with the company. However, this delimitation is developed on the basis of the normal operation of the company in question. However, this delimitation structured based on regular business situations, leaving undefined duties that may be demanded during a situation of financial difficulties.This article will explore how the behaviour of the Board of Directors should be when companies are in the ‘zone of insolvency’ considering the different economic scenarios that may arise in distress situations.